2021
DOI: 10.1002/hep.32183
|View full text |Cite
|
Sign up to set email alerts
|

Insights into modifiable risk factors of cholelithiasis: A Mendelian randomization study

Abstract: Background and Aims:The risk factors of cholelithiasis have not been clearly identified, especially for total cholesterol. Here, we try to identify these causal risk factors. Approach and Results:We obtained genetic variants associated with the exposures at the genome-wide significance (p < 5 × 10 −8 ) level from corresponding genome-wide association studies. Summary-level statistical data for cholelithiasis were obtained from FinnGen and UK Biobank (UKB) consortia. Both univariable and multivariable Mendelian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
118
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(125 citation statements)
references
References 53 publications
5
118
0
2
Order By: Relevance
“…Finally, we assessed the power of remaining SNPs using the F statistics (F = beta 2 /se 2 ) for each SNP. SNPs with less statistical power would be removed to avoid weak instrumental variables (F statistics <10) ( Chen L. et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Finally, we assessed the power of remaining SNPs using the F statistics (F = beta 2 /se 2 ) for each SNP. SNPs with less statistical power would be removed to avoid weak instrumental variables (F statistics <10) ( Chen L. et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…The number of IVs for each exposure varied from 12 (long sleep duration) to 196 (chronotype). The F statistic for each SNP was greater than the empirical threshold of 10 ( Chen et al, 2022 ) and the overall F statistic for each exposure was larger than 10 as well, suggesting the results were less likely to be biased by the weak instruments. The MR Steiger test indicated that each IV explained more variance in exposure than that of the outcome, meaning the results might not be biased by the reverse causation.…”
Section: Resultsmentioning
confidence: 84%
“…Cholelithiasis (gallstone disease) affects approximately 10%~20% of adults globally and is among the hepatobiliary diseases associated with the highest socioeconomic costs. 17 , 18 In addition, cholelithiasis is also an important risk factor for gallbladder cancer, and it is increasingly recognized as a public health concern that needs more attention. 17 , 19 Although epidemiological studies have identified risk factors associated with cholelithiasis, primary prevention remains weak.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 18 In addition, cholelithiasis is also an important risk factor for gallbladder cancer, and it is increasingly recognized as a public health concern that needs more attention. 17 , 19 Although epidemiological studies have identified risk factors associated with cholelithiasis, primary prevention remains weak. 3 We found that there are few individual-based risk prediction models for cholelithiasis.…”
Section: Discussionmentioning
confidence: 99%